Clinical Efficacy of House Dust Mite-specific Immunotherapy in Asthmatic Children - Tzu-Chun Tsai; Jen-Her Lu; Shu-Jen Chen; Ren-Bin Tang (Elsevier, 2010)
Immunotherapy has been widely used in the treatment of allergic diseases. We evaluated the clinical efficacy of specific immunotherapy with extracts of Dermatophagoides pteronyssinus (Dp) and Dermatophagoides farinae (Df) in children with asthma. Methods: All 40 children had moderate-to-severe asthma and positive allergen tests for Dp and Df. All required daily medication. They were randomly assigned to two groups: Half of them received immunotherapy with subcutaneous injections of Dp and Df extracts, while the other half were not given immunotherapy. Participants were followed up for more than 6 months. Results: Children in both groups had apparent improvements in medication use and symptoms after 6 months. The mean medication scores declined from 3.6 ± 1.14 to 1.7 ± 0.66 in the immunotherapy group (p < 0.01) and from 3.35 ± 0.87 to 2.4 ± 1.09 in the control group (p < 0.01). There was a significant difference between the two groups (mean difference 0.95; p < 0.01). The symptom score improved in the immunotherapy group from 2.65 ± 0.98 to 1.20 ± 1.00 (p < 0.01) and in the control group from 2.55 ± 0.99 to 1.40 ± 0.88 (p < 0.01), with a significant difference between the two groups (mean difference 0.3; p < 0.01). The number of office visits in the immunotherapy group was greater than that of the controls, but the frequencies of emergency room visits and hospitalization decreased. Conclusion: Our study showed that specific immunotherapy with Dp and Df was beneficial for asthmatic children.